Quantitative Multiparameter Evaluation of Vacuoles in Intraocular Lenses Employing a High-Magnification Digital Microscopy Method - Vincent Spiezio; Bennett N. Walker; Don Calogero; Ilko K. Ilev (Journal of Ophthalmology)
As small imperfections with micrometric sizes, fluid-filled vacuoles, also referred to as glistenings, in intraocular lenses (IOLs) have been known to induce significant unwanted light scattering that in several cases presumably cause complaints and sometimes lead to IOL explantation and replacement. This unwanted scatter is of particular concern for patients viewing bright light in reduced-light conditions such as when driving at night, as the scattered light toward the retina can cause temporary blindness. In this study, we have developed and implemented an accurate test methodology based on a high-magnification digital microscopy approach for quantitative multiparameter evaluation and classification of IOL vacuoles depending on their critical optical characteristics including vacuole size, density, shape, and orientation within the IOL material. Using the multiparameter database developed by evaluating vacuole characteristics, we established a classification grading system that can be used to evaluate vacuole effects on light scattering.